COVID-19 effects on risk minimising portfolio of transportation and logistics assets / Mohd Azdi Maasar ... [et al.] - Maasar, Mohd Azdi; Jamil, Sallehudin Ayub; Md Arsad, Nur Nadia; Abdullah, Siti Zuraini (UiTM Cawangan Negeri Sembilan, 2021)
The global COVID-19 pandemic has significantly impacted Malaysia's stock market in almost every sector. Transportation and logistics assets are some of the major industries that have been affected by the outbreak. This study considers portfolios of investment that contain transportation and logistics assets in Malaysia, where the aim is to minimise the risk of these portfolios by using the mean-CVaR optimisation model (see [1] for model construction). We also compare the risk behaviours of these portfolios in two different time frames: 1. Before- and 2. Duringthe COVID-19 outbreak with conditional value at risk (CVaR) as a risk measure. Thus, we implement mean-CVaR0.05 on the transportation and logistics assets for: (a) before COVID-19 (B-portfolios); and (b) during COVID-19 (D-portfolios). The randomness of return distributions for each asset is obtained by simulating the monthly scenario returns of 18 transportation and logistics companies listed in Bursa Malaysia from January 2009 until December 2020. Ten optimal (in-sample) portfolios are obtained by minimising the risk using the mean-CVaR optimisation model with three target returns of 0.1%, 0.5%, and 1%, representing low, medium, and high returns, respectively. The risk behaviours of these portfolios are validated by using the out-of-samples analysis.